Supporting Small Medium and Micro Enterprises in South Africa - Tsoabisi, Sello (Mediterranean Journal of Social Sciences, 2012)
The Local Government sphere in South Africa faces several cogent developmentalchallenges. Several interventions have been introduced to confront these challenges, whichinclude poverty, unemployment and skills shortage, with partial success. In this article, aconceptual framework is proposed for small, medium and micro enterprises (SMMEs) inSouth Africa. The literature review includes an analysis of documents issued by fourmunicipalities as well by the former national Department of Provincial and LocalGovernment. In this regard, an explanation of the concept of SMMEs is provided so as tocontextualise the study. Apart from the lack of funding, SMMEs appear to suffer from a lackof information, efficient production technologies, and the inadequate use of managementand control systems. To further contextualise this study, the debate on local economicdevelopment (LED) in the South African local government sphere is presented to highlightthe current challenges. Common characteristics of LED and SMMEs are also enunciated soas to establish the nexus. Finally, drawing from the above context and discussions, aconceptual framework is articulated and presented, which is intended to assistmunicipalities to ensure that viable SMME strategies are developed.